Mobile Learning Design and Its Role in Fostering Critical Thinking in Informatics Education - Rizky Gabriella Sandy; Arico Ayani Suparto; Dyan Yuliana (Universitas Hamzanwadi, 2026)
The use of mobile learning in vocational education continues to grow; however, its implementation often emphasizes technological development without sufficient attention to instructional organization and learning evaluation. This study aims to develop a Kodular-based mobile learning application and examine its practical feasibility and user acceptance in informatics learning. The research employed a research and development approach with exploratory evaluation, involving 20 vocational high school students selected through purposive sampling. Data were collected using user response questionnaires and learning indicator instruments to capture students’ perceptions of usability, learning support, and cognitive engagement after using the application. The collected data were analyzed using descriptive percentage analysis to illustrate trends related to media feasibility and user acceptance. The results show that all evaluated aspects achieved percentages above 85%, indicating a very good level of practical feasibility and user acceptance, particularly in terms of usability, ease of use, and perceived learning support. These findings suggest that the developed mobile learning application can function as a supportive learning medium in vocational informatics education. This study provides practical insights into the development of mobile learning media that aligns instructional organization with learner needs in vocational learning contexts.